1993
DOI: 10.1021/jo00062a013
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective preparation of .beta.-alkyl-.gamma.-butyrolactones from functionalized ketene dithioacetals

Abstract: An efficient and general enantioselective synthesis of d-alkyl-7-butyrolactones has been developed. The key step of this procedure is an oxazolidinone-directed alkylation of a lithiated ketene dithioacetal that proceeds with excellent regiochemical control and high diastereofacial selectivity. Reductive removal of the chiral auxiliary followed by acid-induced cyclization of the resultant hydroxy ketene dithioacetal gives the enantiomerically pure d-alkyl-7-butyrolactone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0
3

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(52 citation statements)
references
References 0 publications
0
49
0
3
Order By: Relevance
“…This new practical route to the heterocycles in the title provides building blocks for the synthesis of natural products and biologically active substances such as alkaloids, macrocyclic antibiotics, lignans, pheromones, and fragrances. [5] Inspired by the work of Whitby et al [6] and Scholz et al, [7] we investigated the use of zirconocene-1-aza-1,3-diene complexes as homoenolate equivalents [8] in stereoselective synthesis. Scholz et al had shown that acetophenone inserts into the Zr ± C s bond of 2,2-bis(h 5 -cyclopentadienyl)-1-(2-methylphenyl)-3-phenyl-1-aza-2-zircona-4-cyclopentene (2).…”
mentioning
confidence: 99%
“…This new practical route to the heterocycles in the title provides building blocks for the synthesis of natural products and biologically active substances such as alkaloids, macrocyclic antibiotics, lignans, pheromones, and fragrances. [5] Inspired by the work of Whitby et al [6] and Scholz et al, [7] we investigated the use of zirconocene-1-aza-1,3-diene complexes as homoenolate equivalents [8] in stereoselective synthesis. Scholz et al had shown that acetophenone inserts into the Zr ± C s bond of 2,2-bis(h 5 -cyclopentadienyl)-1-(2-methylphenyl)-3-phenyl-1-aza-2-zircona-4-cyclopentene (2).…”
mentioning
confidence: 99%
“…It was originally achieved by formation of the lithium salt of the oxazolidin-2-one with n-butyllithium, followed by addition of the acid chloride. [12] Recently, a different procedure was envisaged to eliminate the use of n-butyllithium; the oxazolidin-2-one may be efficiently acylated with a mixed anhydride using triethylamine and a slight molar excess of lithium chloride. [13] In our case we had to perform a homo-oligomerization, so that the acylation source was the 2-oxooxazolidine-4-carboxylate itself.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…66 (Esquema 24) utilizaram basicamente a mesma sequência, na qual introduziram uma etapa de desprotonação enantiosseletiva 67a-b, 68 , obtendo dessa maneira a β-piperonil-γ-butirolactona em sua forma óticamente pura 69 . Correia e cols.…”
Section: Esquema 21unclassified